Kinetics of the formation of protective slag layers on MgO–MgAl2O4–C ladle bricks determined in laboratory. Issue 1 (January 2020) - Preisker, Theresia; Gehre, Patrick; Schmidt, Gert; Aneziris, Christos G.; Wöhrmeyer, Christoph; Parr, Christopher
Abstract: Carbon-bonded magnesia and magnesia-alumina bricks are the state of the art lining materials of the sidewalls and the bottom of steel ladles. Industrial trial tests revealed, that a new generation of MgO–MgAl2 O4 –C bricks, where pre-reacted spinel is added in form of a new calcium magnesium aluminate (CMA) raw material, exhibit a longer service life caused by an enhanced corrosion resistance due to the formation of a protective slag layer. In terms of this work, laboratory corrosion tests have been performed in order to mimic the protective slag layer formation and to study the kinetics of the formation. It has been found that the formation highly depends on the amount of iron present in the melt, which leads to the precipitation of the brownmillerite-phase. Furthermore, the study was extended to force the formation of protective slag layers of different composition which are reliable at higher temperatures and wider temperature ranges by targeted adaption of the brick composition. Cup tests showed that there is a potential to manipulate the composition of a protective slag layer by targeted adaption of the brick composition. Especially MgO, Al2 O3, Fex Oy, and SiO2 from the brick or slag enrich at the slag/refractory-interface.